Upregulating Nrf2 in the RVLM ameliorates sympatho-excitation in mice with chronic heart failure - Ma, Anyun (Free Radic Biol Med, 2019)
Nuclear factor E2-related factor 2 (Nrf2) is a key transcription factor that maintains redox homeostasis by governing a broad array of antioxidant genes in response to oxidant stress. We hypothesized that overexpression of Nrf2 in the rostral ventrolateral medulla (RVLM) ameliorates sympatho-excitation in mice with coronary artery ligation-induced chronic heart failure (CHF). To address this, we overexpressed Nrf2 in the RVLM using an HIV-CamKIIa-Nrf2 lenti virus in C57BL/6 mice. In addition, we used a Lenti-Cre virus in Keap1(flox/flox) mice to upregulate Nrf2 non-selectively in the RVLM. Arterial blood pressure (AP), heart rate (HR), and renal sympathetic nerve activity (RSNA) were recorded under conscious and anesthetized conditions, respectively. Protein expression was assayed using western blotting and immunofluorescence staining. We found that (1) Nrf2 and two target proteins, NQO1 and HO-1 in the RVLM were significantly lower in CHF compared to Sham mice. Nrf2 viral transfection of the RVLM upregulated Nrf2 protein. (2) Urinary NE excretion in CHF mice was markedly attenuated following Nrf2 upregulation (812 ± 133 vs 1120 ± 271 ng/24hr mean±SE, *p < 0.05, n = 8/group). (3) In the conscious state, CHF mice overexpressing Nrf2 exhibited an enhancement in spontaneous baroreflex gain and in phenylephrine-induced baroreflex control of HR. (4) Acute experiments under anesthetisa revealed a significant decrease in basal RSNA (44.0 ± 6.5 vs 64.7 ± 8.3 % of Max. *P < 0.05 n = 8/group) and enhancement in baroreflex sensitivity (Maximal gain −1.8 ± 0.3 vs 1.1 ± 0.2 of mmHg. **p < 0.01. n = 6/group) in CHF mice that were virally transfected with Nrf2 compared with CHF mice transfected with Lenti-GFP. Finally, Lenti-Cre viral overexpression of Nrf2 in Keap1(flox/flox) mice reduced Keap1 protein and increased Nrf2, NQO1, and HO-1 in the RVLM of Sham and CHF mice. CHF-Cre mice exhibited a significant decrease in baseline RSNA and plasma NE concentration (8.9 ± 1.1 vs 12.7 ± 0.9 ng/mL. *P < 0.05 n = 6/group) as compared with CHF-GFP mice. Based on the above data, we conclude that upregulating Nrf2 selectively in the RVLM attenuates sympatho-excitation in CHF mice. Nrf2 may be an important central target for autonomic modulation in cardiovascular disease and during stress.